International Capital Structure Equilibrium. - Hodder, James E; Senbet, Lemma W (Journal of Finance, 1990)
This paper develops a theory of capital structure in an international setting with corporate and personal taxes. The authors generalize the analysis of M. M. Miller (1987) to an international equilibrium characterized by differential international taxation and inflation in otherwise perfect international capital markets. The authors' analysis highlights the key role that corporate tax arbitrage plays in generating an international capital structure equilibrium, and they set forth a number of mechanisms for tax arbitrage transactions. They close the paper by outlining some implications of their analysis for national differences in capital structure, the international Fisher effect, and international tax effects on yield differentials.